Using the Rasch Model to Develop a Measure of Students’ Problem Solving Ability in Optical Instruments - Vera, Rosi; Kaniawati, Ida; Utama, Judhistira Aria (Jurnal Pendidikan MIPA, 2023)
This study aims to develop a test instrument for problem-solving abilities in the material of optical instruments. The research method used is the development of a 4D model consisting of defining, designing, developing, and disseminating. Participants in this study consisted of 75 consisting of 40 males and 35 females in grade 12 high school sciences program at a high school in Bandung. Based on the results of the analysis, it was obtained: (1) expert validation with a CVR index value of 1 and the test instrument included in the valid category, (2) construct validation using Rasch was declared valid, (3) the reliability of each item using Rasch analysis was declared reliable with Cronbach alpha of 0.96, and (4) the difficulty level of the items is evenly distributed at each level of difficulty. Therefore, the test instrument that has been developed can measure students' problem-solving abilities in the material of optical instruments. Keywords: pemodelan Rasch, problem solving ability, optical instruments. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp419-431